PENGGUNAAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA TENTANG BUDAYA DAERAH INDONESIA DI KELAS V SD INPRES SIKUMANA 3 KOTA KUPANG : Penelitian Tindakan Kelas - Sasi, Selviana Fransiska; Taneo, Silvester P.; Kota, Martha K. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to improve student learning outcomes on the topic of Indonesian regional culture through the application of the Guided Inquiry learning model. The research was conducted at SD Inpres Sikumana 3, involving 24 fifth-grade students as research subjects. Data collection techniques included observation and testing, while data analysis was carried out using descriptive quantitative methods by calculating the percentage of learning mastery. The results showed that in Cycle I, 14 students (58.34%) achieved learning mastery, while 10 students (41.66%) did not. Students who achieved mastery were focused during the learning process, actively participated in group discussions, and were able to complete the tasks correctly. Meanwhile, students who did not achieve mastery tended to be less focused, frequently disrupted their peers, and were less involved in group work. In Cycle II, there was a significant improvement, with all students (100%) achieving mastery. This improvement occurred as students became more focused, refrained from disturbing others, and engaged more actively in the learning activities. The conclusion of this study is that the Guided Inquiry learning model is proven to be effective in improving student learning outcomes on the topic of Indonesian regional culture.